2005
DOI: 10.1645/ge-491r.1
|View full text |Cite
|
Sign up to set email alerts
|

Kudoa Iwatai (Myxosporea: Multivalvulida) in Wild and Cultured Fish in the Red Sea: Redescription and Molecular Phylogeny

Abstract: Gilt-head sea bream, Sparus aurata L., the Mediterranean's most important mariculture species, has been cultured for the last 30 yr in Eilat (Israeli Red Sea). Kudoa sp. was the first myxosporean parasite reported from this species. In recent years, an increase in prevalence in both land-based and sea-cage facilities in Eilat has been observed. Infections with the same Kudoa species appeared in cultured European sea bass Dicentrarchus labrax (L.) and grey mullet Mugil cephalus in the same farms, as well as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 30 publications
6
55
1
2
Order By: Relevance
“…The spore dimensions produced in freshwater hosts in this study are comparable with those previously reported from sea bream, red drum and various other aquarium-held host species (Diamant et al 1994, Diamant 1998, Padrós et al 2001. Some morphometric variability has been reported for Enteromyxum leei, assumed to be a result not only of spore fixation method but also of differences in host, a phenomenon addressed by several authors (Kovaleva et al 1979, Diamant 1998, Padrós et al 2001, Diamant et al 2005. Thus, for standardization purposes, measurement of fresh spores should be the preferred method.…”
Section: Discussionsupporting
confidence: 86%
“…The spore dimensions produced in freshwater hosts in this study are comparable with those previously reported from sea bream, red drum and various other aquarium-held host species (Diamant et al 1994, Diamant 1998, Padrós et al 2001. Some morphometric variability has been reported for Enteromyxum leei, assumed to be a result not only of spore fixation method but also of differences in host, a phenomenon addressed by several authors (Kovaleva et al 1979, Diamant 1998, Padrós et al 2001, Diamant et al 2005. Thus, for standardization purposes, measurement of fresh spores should be the preferred method.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, some of the differences in dimensions observed here for K. alliaria from M. magellanicus could also be accounted for by variation between hosts. Similar morphological variation between hosts and locations has been shown for Kudoa iwatai (Diamant et al 2005). However, as other studies indicate, it is equally likely that morphologically distinct spores from different hosts can represent separate Kudoa species (Whipps et al 2003.…”
Section: Resultssupporting
confidence: 76%
“…This sequence was compared to those of other related Kudoa species as determined from previous analyses (Blaylock et al 2004, Abollo et al 2005, Diamant et al 2005) and using the basic local alignment search tool (BLAST) on GenBank (Altschul et al 1990). Sequences were aligned with Clustal X (Thompson et al 1997) and pairwise sequence similarities were generated with BioEdit version 7.0.5 (Hall 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Infections can result in post-mortem myoliquifaction and render fillets unmarketable (Moran et al 1999). In the Red Sea, native K. iwatai produced heavy infections in gilt head sea bream (Sparus aurata) when this fish species was introduced from the Mediterranean for cage culture (Diamant et al 2005). In Japan, heavy outbreaks of native K. amamiensis occurred in exotic yellowtail (Seriola quinqueradiata) and amberjack (S. dumerilii) (Sugiyama et al 1999).…”
Section: Aquaculture and Mariculturementioning
confidence: 99%